Konsep Kebahagiaan Menurut Ibn al-Haytham - Usep Mohamad Ishaq (Islamica: Jurnal Studi Keislaman, 2020)
Ibn al-Haytham (965-1039) is so far known merely as a mathematician and scientist. It is understand-able because most of his available works at this time are on mathematics and science. As a result, researches on his philosophical, psychological, and theological thought are still lacking. This paper discusses Ibn al-Haytham’s philosophy of happiness, using historical research method by collecting and analyzing his works linguistically, particularly his Kitāb Thamarat al-Ḥikmah. The results reveal that Ibn al-Haytham, as well as Muslim philosophers of his time, accepted the concept of happiness from Greek philosophers, such as Socrates, Plato and Aristotle. However, he incorporated religio-metaphysical dimensions to his concept of happiness. This finding shows that Ibn al-Haytham is not only a mathematician and scientist, but also a philosopher like al-Fārābī, Ibn Miskawayh, and al-Ghazālī.